2022
DOI: 10.2337/db21-0382
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Regulate Pancreatic Growth, Exocrine Function, and Gut Hormones

Abstract: Growing evidence indicates an important link between gut microbiota, obesity, and metabolic syndrome. Alterations in exocrine pancreatic function are also widely present in patients with diabetes and obesity. To examine this interaction, C57BL/6J mice were fed either a chow diet, high-fat diet (HFD) or HFD plus oral vancomycin or metronidazole to modify the gut microbiome. HFD alone leads to a 40% increase in pancreas weight, decreased glucagon-like peptide-1 and peptide YY levels, and increased glucose-depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In addition to the relationship between the oral microbiome and pancreatic function, alterations in pancreatic functions can directly affect the profile of the gut microbiome by inducing changes in metabolite production. Impaired exocrine pancreatic function is the most prominent host factor affecting the composition and diversity of the human intestinal microbiome ( Frost et al., 2019 ; Girdhar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the relationship between the oral microbiome and pancreatic function, alterations in pancreatic functions can directly affect the profile of the gut microbiome by inducing changes in metabolite production. Impaired exocrine pancreatic function is the most prominent host factor affecting the composition and diversity of the human intestinal microbiome ( Frost et al., 2019 ; Girdhar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is a complex, dynamic, spatially heterogeneous ecosystem that collectively maintains the normal physiological dynamic balance of the human body. Animal studies using transplanted fecal microorganisms in germ-free mice have shown that gut microbiota play an important role in bone metabolism [ [112] , [113] , [114] ] and blood sugar regulation [ 115 , 116 ]. Additionally, the composition and abundance of healthy microbiota reflect the intestinal mucosal barrier effect, the production of major metabolites such as SCFAs, and the promotion of unbound secondary bile acid formation, which are common factors for alleviating T2DM and promoting bone health.…”
Section: Dietary Fiber and Gut Microbiotamentioning
confidence: 99%
“…Li et al added the commensal bacterium Alistipes onderdonkii to obese mice induced by HFD and found a reduction in hyperglycemia and alleviation of HFD-induced inflammation and glucose intolerance ( 143 ). Another study revealed that HFD could induce pancreatic acinar cell proliferation through gut microbiota, resulting in a 40% increase in pancreatic weight, alterations in pancreatic secretion, as reflected by decreased levels of GLP-1 and peptide YY, increased levels of glucose-dependent insulinotropic polypeptide, and changes in 32 host proteins within the gut, with pancreatic enzymes showing the most significant changes ( 214 ). Further research utilizing lipid-induced mice fed with HFD demonstrated that adding broccoli to the diet led to alterations in the diversity and structure of Proteobacteria, Akkermansia , and Mucispirillum schaedleri in the gut, improving insulin resistance ( 215 ).…”
Section: Targeting Gut Microbiota Modulation For Metabolic Disorders ...mentioning
confidence: 99%